Pemanfaatan sampah rumah tangga berbasis pengelolaan bank sampah di sekolah - Abdul Rahim; Ibrahim Ibrahim; Nur Indah Mansyur (IKIP PGRI Bojonegoro, 2020)
ABSTRACTThis community service activity aims to provide education about household waste utilization through waste banks in schools. The method used in this community service activity is training and mentoring on how to use waste and manage waste through a waste banks. The results of this activity show: (1) increasing students' insights about household waste utilization by composting and liquid fertilizer training; (2) students and schools get experience on waste bank management; (3) through the management of a waste banks, transactions that occur reach Rp.2,231,030 in SMP Negeri 2, and Rp. 138,000 at SDN 08 Tarakan. The evaluation of this activity is based on the number of customers and the value of the transaction. So the model of managing a waste banks in junior high schools can be applied, but it is not recommended for primary schools in Tarakan City.Â Keyword: Waste, School, waste banks.Â ABSTRAKKegiatan pengabdian ini bertujuan untuk memberikan edukasi tentang pemanfaatan sampah rumah tangga melalui bank sampah di sekolah. Metode yang digunakan dalam kegiatan pengabdian ini yakni pelatihan dan pendampingan bagaimana pemanfaatan sampah dan pengelolaan sampah melalui bank sampah. Hasil kegiatan ini menunjukkan: (1) meningkatnya wawasan siswa tentang pemanfaatan sampah rumah tangga dengan pelatihan kompos dan pupuk cair; (2) siswa dan pihak sekolah mendapatkan pengalaman tentang pengelolaan bank sampah; (3) melalui pengelolaan bank sampah, transaksi yang terjadi mencapai Rp 2.231.030 di SMP Negeri 2, dan Rp. 138.000 di SDN 08 Tarakan. Evaluasi kegiatan ini berdasarkan jumlah nasabah dan nilai transaksi. Jadi model pengelolaan bank sampah di SMP dapat diterapkan, namun tidak direkomensasikan untuk sekolah dasar di Kota Tarakan.Â Kata Kunci: Sampah, Sekolah, Bank Sampah.